Hermeneutika Hadis Khaled M. Abou El Fadl - Suhendra, Ahmad (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2015)
This paper reviews the hermeneutic Khaled M. Abou El-Fadl, in his work entitled Speaking God’s Name: Authority and Women. This figure is interesting to study because his theory stems from the fact that they experienced. At first he was an admirer salafi, then criticize ideologies. This paper focuses on the thoughts on the meaning and religious texts. To unload thinking Khaled used descriptive-analytical method. Apparently, hermeneutics offered Khaled influenced by several prominent Western hermeneutics, especially Gadamer and Gracia. From there, he formulated the five preconditions which adopted in interpreting the sacred text of someone’s religion.